Pengaruh Kombinasi Pursed Lip Breathing Exercise dan Posisi High Fowler 90° terhadap Pertukaran Gas pada Pasien Tuberkulosis Paru - Dini Al Hamdany; Nutrisi Nu’im Haiya; Moch Aspihan (PPNI UNIMMAN, 2026)
Pulmonary tuberculosis is a chronic infectious disease that can cause impaired gas exchange due to lung tissue damage, increased mucus production, and decreased lung elasticity. This condition may lead to shortness of breath, decreased oxygen saturation, and ineffective breathing patterns. Non-pharmacological nursing interventions such as pursed lip breathing exercise and body positioning are needed to improve respiratory function. The combination of pursed lip breathing exercise and the high Fowler position is expected to enhance alveolar ventilation and improve oxygenation in patients with pulmonary tuberculosis.Method: This study is a quantitative research with a pre-experimental/quasi-experimental design using a pre-test and post-test approach. The sample consists of pulmonary tuberculosis patients who experience impaired gas exchange and meet the inclusion criteria. The intervention provided is a combination of pursed lip breathing exercise and the high Fowler position. Gas exchange is measured by assessing oxygen saturation and respiratory rate before and after the intervention. Data will be analyzed using appropriate statistical tests to determine the effect of the intervention.Results: The expected results of this study are an increase in oxygen saturation and improvement in respiratory rate after the application of the combination of pursed lip breathing exercise and the high Fowler position in patients with pulmonary tuberculosis.Conclusion: The combination of pursed lip breathing exercise and the high Fowler position is expected to have a positive effect on improving gas exchange in patients with pulmonary tuberculosis and can be applied as an independent nursing intervention in clinical practice.